2019
DOI: 10.3390/en12163067
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Viscosity Prediction of Water-Based Muds Using Empirical Correlation and an Artificial Neural Network

Abstract: Apparent viscosity is of one of the main rheological properties of drilling fluid. Monitoring apparent viscosity during drilling operations is very important to prevent various drilling problems and improve well cleaning efficiency. Apparent viscosity can be measured in the laboratory using rheometer or viscometer devices. However, this laboratory measurement is a time-consuming operation. Thus, in this paper, we have developed a new empirical correlation and a new artificial neural network model to predict th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…According to the above theories, artificial intelligence methods are used to estimate rheological properties more accurately in real time based on parameters such as the Marsh funnel viscosity, mud weight, and solid content [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Bispo et al [ 72 ] used temperature, xanthan gum, bentonite, and barite to estimate AV.…”
Section: Real-time Measurement Technologiesmentioning
confidence: 99%
“…According to the above theories, artificial intelligence methods are used to estimate rheological properties more accurately in real time based on parameters such as the Marsh funnel viscosity, mud weight, and solid content [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Bispo et al [ 72 ] used temperature, xanthan gum, bentonite, and barite to estimate AV.…”
Section: Real-time Measurement Technologiesmentioning
confidence: 99%
“…This gel structure is formed by the interaction of drilling fluid components and it mainly depends on the size, concentration, and electrostatic charge of the solid particles like (clay and nanoparticles). This property should be carefully monitored to preserve solids without causing extreme recirculation pressure through the mud pumps start up [2] Generally, the gel strengths are measured by a rotational viscometer after the mud has set gently for two different periods of time (ten seconds and ten minutes).…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…Then it returns back to the surface through the annular space between the drilling string and the borehole [1]. Primarily, drilling fluids are used for cooling down and lubricating the drilling bit and the drilling string, suspend the rock cutting when the circulation paused, carrying the rock cutting from borehole to the surface, maintaining the hydrostatic head pressure (Ph) greater than the pore pressure (Pf) to avoid any kind of unwanted formation fluids to flow to the well [2], [3] Generally, drilling mud design is on the most essential aspects to consider during the well construction and completion stages. The proper selection of the drilling mud is one of the key factors for succussing any drilling operation, which is typically based on its performance, cost, and environmental influence.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Khdheeawi and Mahdi [35] applied an ANN to predict the apparent viscosity of water-based drilling fluid using the mud density and Marsh funnel time. They concluded that the developed ANN correlation could predict AV with an average absolute percentage error (AAPE) of 8.6% and a correlation coefficient of 98.8%.…”
Section: Artificial Neural Networkmentioning
confidence: 99%